Interações inseticidas e iscas tóxicas em Ceratitis capitata (Diptera: Tephritidae) e suas implicações na macrofauna do solo - Salustino, Angélica da Silva (2023)
Insecticides are of great importance for the development of agricultural productivity, especially in the fruit sector, which requires a large number of applications for the control of insect pests, such as Ceratitis capitata (Wiedemann, 1824) (Diptera: Tephritidae). Among the products most used to control this pest are those of organophosphate groups, pyrethroids and spinosyns, which are applied through total coverage or through the use of toxic baits. However, the high use of these products can cause negative effects to the environment and its biota, mainly to soil organisms. Thus, this study aimed to evaluate the susceptibility of C. capitata to malathion, deltamethrin and spinetoram doses in isolation and in the formulation of toxic baits, and the effects of these insecticides on soil macrofauna. The evaluation of the lethality of the insecticides in isolation was carried out on the immature stages and the adults of C. capitata, via contact and via ingestion, applying doses obtained by decreasing the recommended dose in intervals of 20%, this being the minimum dose used. The evaluated parameters were: (1) viability of eggs and (2) of pupae and (3) mortality of larvae and (4) of adults. When the products were associated with the attractants, forming toxic baits, the flies were offered mixtures with the insecticides at the dose recommended by the manufacturer (D100) and a dose of 80% of the recommended dose (D80). After offering the baits to the insects, their toxicity was evaluated as a function of time. To evaluate the effect of insecticides on macrofauna, they were applied at the dosage recommended by the manufacturer, using twice the volume of spray for terrestrial applications. After application, the soil macrofauna was evaluated based on the Tropical Soil Biology and Fertility (TSBF) method, with subsequent determination of density (individuals per m²), richness, Shannon-Weaver diversity indices (H') and soil evenness. Pielou (J'). As a result, in applications using only insecticides, it was observed that spinetoram and malathion, when applied via contact, caused high mortality in adults, with LD90 at subdoses of 43.74% (52.48 g p.c. ha-1) and 68 .81% (137.62 ml p.c. 100L-1), respectively. For the egg phase, only the defensive with deltamethrin presented LD50. The stages of larvae and pupae did not suffer negative effects from contact doses, however, they were affected by insecticides, when larvae showed a mortality of 52% for spinetoram and 61% for malathion. By ingestion, it was only possible to estimate the LD50 with malathion and deltamethrin in adults, for larvae the lethality was below 20% with the three insecticides. With the use of toxic baits, higher rates of susceptibility of C. capitata were observed in formulations with malathion at D80 in a median lethal time (TL50) of 1 hour, regardless of the attractant used. As for the baits formulated with spinetoram, a 6-hour TL50 at D80 was observed. In contrast, the lowest susceptibility was observed in baits formulated with deltamethrin, regardless of the dose and attractant used. For the effects on soil macrofauna, it was found that malathion, deltamethrin and spinetoram did not affect the total density nor the density by taxonomic groups, except in the Coleoptera group, which showed a lower density of individuals per m2 in soil treated with malathion and deltamethrin. The diversity of individuals in the evaluated groups was also reduced by deltamethrin. Finally, it can be stated that deltamethrin has low efficiency in the control of C. capitata adults, via direct contact and with the use of toxic baits. Spinetoram and malathion have an efficiency of 90% on C. capitata at subdoses of 43.74% (52.48 g p.c. ha-1) and 68.81% (137.62 mL p.c. 100L-1) respectively, via direct contact. In formulations of toxic baits, malathion and spinetoram remain efficient in controlling C. capitata, even with a 20% reduction in the dose recommended by the manufacturer of each product, and can be formulated withBiofruit®, with Cera Trap® and with sugarcane molasses -de-sugar without compromising the expected result. In the field, malathion and deltamethrin applications reduce the density of Coleoptera populations and the diversity of soil macrofauna under the tested conditions.